IODP workshop: developing scientific drilling proposals for the Argentina Passive Volcanic Continental Margin (APVCM) – basin evolution, deep biosphere, hydrates, sediment dynamics and ocean evolution - Flood, Roger D. (2017)
The Argentine margin contains important sedimentological, paleontological and chemical records of regional and local tectonic evolution, sea level, climate evolution and ocean circulation since the opening of the South Atlantic in the Late Jurassic–Early Cretaceous as well as the present-day results of post-depositional chemical and biological alteration. Despite its important location, which underlies the exchange of southern- and northern-sourced water masses, the Argentine margin has not been investigated in detail using scientific drilling techniques, perhaps because the margin has the reputation of being erosional. However, a number of papers published since 2009 have reported new high-resolution and/or multichannel seismic surveys, often combined with multi-beam bathymetric data, which show the common occurrence of layered sediments and prominent sediment drifts on the Argentine and adjacent Uruguayan margins. There has also been significant progress in studying the climatic records in surficial and near-surface sediments recovered in sediment cores from the Argentine margin. Encouraged by these recent results, our 3.5-day IODP (International Ocean Discovery Program) workshop in Buenos Aires (8–11 September 2015) focused on opportunities for scientific drilling on the Atlantic margin of Argentina, which lies beneath a key portion of the global ocean conveyor belt of thermohaline circulation. Significant opportunities exist to study the tectonic evolution, paleoceanography and stratigraphy, sedimentology, and biosphere and geochemistry of this margin.